Impact of the perception of performance appraisal practices on individual innovative behavior - Teresa Canet-Giner; Ana María Redondo-Cano; Carmen Saorín-Iborra; Naiara Escribá-Carda (European Journal of Management and Business Economics (EJM&BE), 2020)
Purpose The purpose of this paper is to analyze the impact of employees' perception of performance appraisal (PA) practices on innovative behavior (IB). The authors also propose to analyze consistency, a dimension of Human Resource Management (HRM) system strength, as a moderating variable in the aforementioned relationship. Design/methodology/approach A quantitative study was conducted, using a sample of 166 employees carrying out highly qualified, intensive knowledge jobs in four industrial companies in the Valencian region of Spain. The hypotheses were tested by applying the Smart-PLS 3.2 software. Findings The findings confirmed that in a context of professional and qualified work, PA practices have a direct and positive effect on IB. However, the results obtained did not enable us to affirm that employee perceptions of the consistency of the HR system moderated the relationship between PA and IB. Originality/value The paper's originality lies in including the role of consistency, a dimension of HRM system strength, in the analyzed relationship. When employees believe that PA achieves the goals for which this practice was designed, and that this appraisal follows a clear strategic direction over time, they perceive that the assessment system is not arbitrary, i.e., that this HR practice is being applied consistently. Consequently, the present work shows the relevant role of the perception of consistent PA when the firm wants to encourage IB. This fact opens up the field to study how to define and implement control mechanisms that tell managers whether there is a fit between employees' perceptions and the intentionality of the HRP these managers have defined.
Keywords: 650; Performance appraisal; Innovative behaviour; HRM system strength